Melkersson-Rosenthal syndrome associated with psoriasis vulgaris and orofacial impetiginization - Ryszard Galus; Katarzyna Borowska; Marian Jędrych; Barbara Jodłowska-Jędrych; Longin Niemczyk; Marek Antiszko; Stanisław Zabielski (Our Dermatology Online, 2014)
Melkersson-Rosenthal syndrome (MRS) is a disease of unknown etiology, usually restricted to the orofacial region, characterized by reccurent orofacial swelling, relapsing facial palsy and plicated tongue. We report case of MRS associated with psoriasis in a 25-year-old woman. The patient has been treated with satisfying results with a combination of Cetirizine, Cefuroxime axetil and Mupirocin ointment; psoriatic eruptions were successfully treated with 10 % salicylic-sulphuric ointment twice a day. MRS syndrome is a rare disease and should be considered in the differential diagnosis of labial swelling and facial palsy.